Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ñ‚Ð¾Ñ‚Ð°Ð»ÑŒÐ½Ð¾Ð³Ð¾ ÐºÑ€Ð¸Ð¾Ð²Ð¾Ð·Ð´ÐµÐ¹ÑÑ‚Ð²Ð¸Ñ Ð½Ð° Ñ€Ð°Ð½Ð½Ð¸Ðµ ÑÑ‚Ð°Ð´Ð¸Ð¸ Ñ€ÐµÐ¿Ð°Ñ€Ð°Ñ‚Ð¸Ð²Ð½Ð¾Ð³Ð¾ Ð¾ÑÑ‚ÐµÐ¾Ð³ÐµÐ½ÐµÐ·Ð° (ÑÐºÑÐ¿ÐµÑ€Ð¸Ð¼ÐµÐ½Ñ‚Ð°Ð»ÑŒÐ½Ð¾Ðµ Ð¸ÑÑÐ»ÐµÐ´Ð¾Ð²Ð°Ð½Ð¸Ðµ) - Poletayeva, N. Yu.; Kozlov, A. V.; Babijchuk, G. A.; Bengus, L. M.; Ashukina, N. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
Total extreme cryotherapy (TECT) allows to reduce a little bit an inflammation stage in the area of transcortical bone defect of a femur of white rats. Comparison of morphological picture of bone defect site after single and 3 fold TECT to the 7th day after operation has shown, that the most effective is 3 fold Ð¢ÐÐšÐ’ due to which in the defect zone the specific weight of osteogenic fibroreticular tissue not only increases, but also there are observed first signs of the formation of young bone trabeculas in the site of defect bottom.